Evaluation of Periodontal Parameters in Patients with Early Stage Chronic Lymphocytic Leukemia - Nives Rinčić; Darko Božić; Goran Rinčić; Petar Gaćina; Darije Plančak (University of Zagreb. School of Dental Medicine, 2016)
Objective: To assess periodontal conditions in patients with early stage CLL and to compare it with the periodontal status of age matched healthy controls and to analyze the relationship between periodontal and hematological parameters in CLL patients. Materials and Methods: 60 subjects were examined: 30 patients with CLL Rai 0 (test group) and 30 age-matching healthy individuals (control group). The exclusion criteria were: presence of other systemic disease or condition (e.g. diabetes), history of treatment for periodontitis, use of antibiotics during the last 3 months, use of medications. Socio-demographic data were obtained by means of a questionnaire. Participants with at least 8 teeth underwent a full mouth examination assessing API, PBI, PPD, REC and CAL. Medical data for CLL patients were collected from the patients' records, while hematological data were obtained from the hemogram. Results: Difference between groups was statistically significant for age, number of teeth and frequency of dental checkups (p<0.05). Patients with CLL had significantly higher average values of periodontal indices (API 0.81±0.18; PBI 2.72±0.68; PPD 3.40±0.53; REC 1.95±0.87, CAL 4.37±0.80) compared to the control group (API 0.69±0.15; PBI 1.91±0.45; PPD 2.51±0.40; REC 0.99±0.54; CAL 3.00±0.58). The correlation coefficients between age and periodontal indices showed statistically significance between age and REC (r=0.357; p<0.01), and age and CAL (r=0.295; p<0.05). Age was not statistically significant covariate for CAL (F=2.205; p>0.05), only for REC (F=4.601; p<0.05). After the removal of the statistical effect of age, the difference in REC between CLL and control group remained statistically significant (F=19.732; p<0.01; eta2=0.287). Statistically significant association between periodontal and hematological parameters in CLL patients was not found (p>0.05). Conclusion: The results of this study showed that patients with CLL had worse periodontal status compared to healthy subjects. Causal relationship between periodontal and hematological parameters was not proved.